2021
DOI: 10.1016/j.ssmph.2021.100812
|View full text |Cite
|
Sign up to set email alerts
|

Social capital or vulnerability: Which has the stronger connection with selected U.S. health outcomes?

Abstract: We tested associations between social capital or vulnerability and health outcome measures of adult obesity, adult diabetes, and life expectancy at the county level in the United States with data from 2015 to 2018. This ecological cross-sectional study utilized secondary data from four open access databases: The Geography of Social Capital (U.S. Congress, 2018), County Health Rankings (2018), CDC's Behavioral Risk Factor Surveillance System (BRFSS, 2018) and the Kaiser Family Foundation (KFF, 2015). Our depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…A growing number of scholars have linked social capital theory to health outcomes (Murayama et al, 2012;Musalia, 2016;Rodgers et al, 2019;Tomita & Burns, 2013). Borges (Borges et al, 2021) concluded that vulnerability measures were strongly associated with obesity, diabetes, and life expectancy by testing U.S. population health data from 2015-2018 and that social capital had a significant effect on life expectancy. Cronin et al (2021) noted the significant impact of social capital on hospitals in establishing population health partnerships to address health disparities and reduce preventable mortality.…”
Section: Social Capital Perspective Of Ohcmentioning
confidence: 99%
“…A growing number of scholars have linked social capital theory to health outcomes (Murayama et al, 2012;Musalia, 2016;Rodgers et al, 2019;Tomita & Burns, 2013). Borges (Borges et al, 2021) concluded that vulnerability measures were strongly associated with obesity, diabetes, and life expectancy by testing U.S. population health data from 2015-2018 and that social capital had a significant effect on life expectancy. Cronin et al (2021) noted the significant impact of social capital on hospitals in establishing population health partnerships to address health disparities and reduce preventable mortality.…”
Section: Social Capital Perspective Of Ohcmentioning
confidence: 99%